2017
DOI: 10.18632/oncotarget.17575
|View full text |Cite
|
Sign up to set email alerts
|

5azadC treatment upregulates miR-375 level and represses HPV16 E6 expression

Abstract: High-risk human papillomaviruses are the etiological agents of cervical cancer and HPV16 is the most oncogenic genotype. Immortalization and transformation of infected cells requires the overexpression of the two viral oncoproteins E6 and E7 following HPV DNA integration into the host cell genome. Integration often leads to the loss of the E2 open reading frame and the corresponding protein can no longer act as a transcriptional repressor on p97 promoter. Recently, it has been proposed that long control region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…In this study, we confirmed that the treatment of HPV16 positive cancer cell lines with 5azadC leads to the downregulation of E6 at both mRNA and protein levels (7)(8)(9). As expected, a p53 and p21 restoration was observed in treated cells confirming the functional loss of E6.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In this study, we confirmed that the treatment of HPV16 positive cancer cell lines with 5azadC leads to the downregulation of E6 at both mRNA and protein levels (7)(8)(9). As expected, a p53 and p21 restoration was observed in treated cells confirming the functional loss of E6.…”
Section: Discussionsupporting
confidence: 88%
“…The downregulation of E6 was partly due to the upregulation of miR-375 (8,9), known to target the early HPV16 transcripts (10). Indeed, E6 expression was only partially restored by miR-375 inhibitor in 5azadC-treated cells (9).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…miR-375 and miR-139 targeted HPV E6/E7 mRNA in cervical cancer cells. As reported, the mRNA of the HPV E6/E7 gene was targeted by multiple microRNAs, including miR-375 (25,26) and miR-139 (27), in cervical cancer cells. To confirm the targeting effect, mimics of miR-375 were transfected into HeLa cells.…”
Section: Resultsmentioning
confidence: 63%